Efektivitas Penanggulangan Kemiskinan oleh Dinas Sosial di Kota Gorontalo - Sa’ban, Ingki Nurcahayani; Aneta, Asna; Tui, Fenti Prihatini Dance (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aimed to understand and describe the effectiveness of poverty alleviation efforts by the Social Affairs Agency in Gorontalo City. The approach used was qualitative, specifically descriptive research. Data collection methods included interviews, observations, and documentation. Primary data was obtained through interviews with key informants such as the Head of the Program Subdivision from the Social Affairs and Community Empowerment Agency of Gorontalo City, members of the Social Empowerment, Institutional, and Poverty Alleviation Division from the same agency, and 9 beneficiary families (KPM) of the poverty alleviation program. The research findings indicate that poverty alleviation efforts by the Social Affairs Agency in Gorontalo City, measured through four indicators: program targets, program socialization, program achievement, and program monitoring. have been effective. The results show that the efforts to alleviate poverty by the Social Affairs Agency in Gorontalo City have increased the community’s welfare and have been optimally sustained. Considering the achievement of the four effectiveness indicators, namely program targets, program socialization, program achievement, and program monitoring, the poverty alleviation programs have reduced the financial burden of the beneficiary families and assisted them in meeting their daily basic needs.